ANALYSIS OF DAILY AND ANNUAL VARIATIONS OF SOLAR RADIATION, AIR TEMPERATURE, PRECIPITATION, WIND SPEED, HUMIDITY, AND AIR PRESSURE IN LAMPUNG AS INDICATORS OF RENEWABLE ENERGY - Ayu Aprilia; Ahmad Faruq Abdurrahman; Annisa Ananda (Indonesian Journal of Science Education and Applied Science, 2024)
This study aims to analyze the potential for renewable energy development in Lampung Province, Indonesia, using data from NASA POWER and then integrating it with regional geographic and climate characteristics. The analysis focuses on three main types of renewable energy: solar, wind, and hydropower. In solar energy, Pesisir Barat shows significant potential with high and consistent solar radiation levels, averaging 18.61 kWh/m²/day, and stable temperature conditions, making this area suitable for solar photovoltaic (PV) systems. However, Mesuji shows lower solar radiation but remains a candidate for further exploration. Humidity patterns show minimal impact on solar radiation, while stable air pressure improves solar energy prospects in most areas. Based on the analysis, wind energy has limited potential for large-scale projects due to low wind speeds, averaging 1.0–2.5 m/s, but it can be used for micro-scale applications in coastal areas such as the Pesisir Barat and South Lampung. Hydropower presents significant opportunities, particularly in areas with high precipitation and significant topographic variation, such as West Lampung and Tanggamus, which are ideal for large-scale hydropower and micro-hydro systems. Seasonal precipitation patterns and stable air pressure support renewable energy development by providing predictable resource availability.Keywords: Energy, Lampung, NASA POWER. Studi ini bertujuan untuk menganalisis potensi pengembangan energi terbarukan di Provinsi Lampung, Indonesia, dengan menggunakan data dari NASA POWER dan kemudian mengintegrasikannya dengan karakteristik geografis dan iklim regional. Analisis difokuskan pada tiga jenis utama energi terbarukan: tenaga surya, angin, dan tenaga air. Dalam energi surya, Pesisir Barat menunjukkan potensi yang signifikan dengan tingkat radiasi surya yang tinggi dan konsisten, rata-rata 18,61 kWh/m²/hari, dan kondisi suhu yang stabil, menjadikan wilayah ini cocok untuk sistem fotovoltaik surya (PV). Namun, Mesuji menunjukkan radiasi surya yang lebih rendah tetapi tetap menjadi kandidat untuk eksplorasi lebih lanjut. Pola kelembapan menunjukkan dampak minimal pada radiasi surya, sementara tekanan udara yang stabil meningkatkan prospek energi surya di sebagian besar wilayah. Berdasarkan analisis, energi angin memiliki potensi terbatas untuk proyek skala besar karena kecepatan angin yang rendah, rata-rata 1,0–2,5 m/s, tetapi dapat digunakan untuk aplikasi skala mikro di wilayah pesisir seperti Pesisir Barat dan Lampung Selatan. Pembangkit listrik tenaga air menawarkan peluang yang signifikan, terutama di daerah dengan curah hujan tinggi dan variasi topografi yang signifikan, seperti Lampung Barat dan Tanggamus, yang ideal untuk sistem pembangkit listrik tenaga air dan mikrohidro skala besar. Pola curah hujan musiman dan tekanan udara yang stabil mendukung pengembangan energi terbarukan dengan menyediakan ketersediaan sumber daya yang dapat diprediksi.Kata kunci: Energi, Lampung, NASA POWER.